UPAYA BINLUH SATUAN BINMAS MENCEGAH PENYALAHGUNAAN MINUMAN KERAS OLEH PELAJAR SMA DI WILAYAH HUKUM POLRESTA BOGOR KOTA - mochammad fadel hardi putra suhardi (Advances in Police Science Research Journal, 2020)
Adolescence becomes a transitional period to find his true identity. Teenagers still get affected by bad things like liquor abuse. Consumption of liquor is considered to be a cool thing for teenagers. 3 teenagers died from consuming liquor mixed with cough medicine. The binmas Unit has a role in the attempt to handle the case of liquor among high school students with guidance and counseling. This research aims to analyze and describe an effort and factors that influence the performance of binmas units. Research location in Bogor City Polresta with a focus on coaching and counseling. This study uses qualitative methods with descriptive analysis techniques. Using data triangulation (Moleong; 2006: 330) 4 (four) kinds of techniques namely sources, theories and techniques as well as primary, secondary data sources. Data validity is data reduction, data display, conclusion drawing and verification.This research uses crime prevention theory, functionalist theory and behavior theory as well as the concept of counseling and the concept of partnership and cooperation. implementation binluh less than the maximum done by binmas units. in the implementation of there are internal factors that influence it's a personnel factor and many members who have not yet implementation binmas vocational training, and the external factor that affects are still a lot of liquor dealers that still illegally operated, less insight students about danger drinking liquor and surveillance from the school that is still very less in preventing students drink liquor. The conclusion is that inhibiting factors coaching and counseling conducted by the binmas unit it's a member competence, lack of insight students, and there are still many illegal liquor sellers